Intramolecular charge separation in spirobifluorene-based donor-acceptor compounds adsorbed on Au and indium tin oxide electrodes - Heredia, Daniel Alejandro (2013)
Surface photovoltage (SPV) measurements were performed with a Kelvin-probe in spirobifluorene-based donor (diphenylamine)-acceptor (dicyano or cyanoacrylic acid moieties) compounds adsorbed from highly diluted solutions onto Au and indium tin oxide electrode surfaces. Strong intramolecular charge separation (negative SPV signals up to more than 0.1 V) due to directed molecule adsorption was observed only for spirobifluorene donor-acceptor compounds with carboxylic acid moiety. SPV signals and onset energies of electronic transitions depended on ambience conditions.